2008
DOI: 10.1021/jf072660u
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Allergenic Protein Sin a 1 from Yellow Mustard (Sinapis alba L.) Seeds Using Enzyme-Linked Immunosorbent Assay

Abstract: Allergy to yellow mustard (YM; Sinapis alba L.) seed proteins has been reported and is currently seen as a constraint that hampers expansion of YM protein utilization. The most predominant allergenic protein of YM seed has been recognized as Sin a 1. In this study, Sin a 1 was purified ( S. alba var. Andante), rabbit polyclonal antibodies (pAb) specific to Sin a 1 were generated, and a sandwich enzyme-linked immunosorbent assay (S-ELISA) was developed to detect and quantify Sin a 1 from YM. The S-ELISA method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Aluko and McIntosh (2004) demonstrated that 12 and 13 kDa polypeptides were subunits of the napin of mustard seed. Shim and Wanasundara (2008) reported that a single protein band of 14.5 kDa polypeptides were two polypeptide chains of 4.5 and 10 kDa linked by disulfide bonds. From the above information, it was concluded that the bands found in SDS-PAGE were cruciferin and napin, and that they could be extracted with either TS or NaCl solution.…”
Section: Discussionmentioning
confidence: 99%
“…Aluko and McIntosh (2004) demonstrated that 12 and 13 kDa polypeptides were subunits of the napin of mustard seed. Shim and Wanasundara (2008) reported that a single protein band of 14.5 kDa polypeptides were two polypeptide chains of 4.5 and 10 kDa linked by disulfide bonds. From the above information, it was concluded that the bands found in SDS-PAGE were cruciferin and napin, and that they could be extracted with either TS or NaCl solution.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative detection of mustard allergens in food can be accomplished by sandwich-type ELISA with LODs as low as 1  μ g of ground whole mustard seeds per mL [133, 134] or qPCR [111]. …”
Section: Food Ingredients Allergenic Fractions and Recognized Almentioning
confidence: 99%
“…The ELISA method is by far the most common and is routinely employed in various food analysis labs due to its high precision, simple handling and good potential for standardization. Additionally, quantitative data are possible with the ELISA technique (Shim and Wanasundara, 2008). However results generated with the ELISA method must be sometimes taken with caution as substantial differences in the detectable protein from the standard on which the test is based, resulting for example from variations in the processing of the food matrix, might lead to false results.…”
Section: Pcr-based Allergen Detection and Quantification In Food Matrmentioning
confidence: 99%